Pregunta
upstudy study bank question image url

Question 5 Express \( \frac{25}{(x-2)(x+3)^{2}} \) in the form \( \frac{A}{x-2}+\frac{B}{x+3}+\frac{C}{(x+3)^{2}} \) and hence find \( \int \frac{25}{(x-2)(x+3)^{2}} d x \)

Ask by Perkins Craig. in the United Kingdom
Feb 23,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The integral of \( \frac{25}{(x-2)(x+3)^2} \) with respect to x is \( \ln\left|\frac{x-2}{x+3}\right| + \frac{5}{x+3} + C \).

Solución

We wish to write   25/[(x – 2)(x + 3)²] = A/(x – 2) + B/(x + 3) + C/(x + 3)². Step 1. Multiply both sides by (x – 2)(x + 3)² to remove denominators:   25 = A(x + 3)² + B(x – 2)(x + 3) + C(x – 2). Step 2. Find A, B, and C. • Choose x = 2:   25 = A(2 + 3)² + B(2 – 2)(2 + 3) + C(2 – 2)   ⇒ 25 = A(5)²   ⇒ 25 = 25A  ⟹ A = 1. • Choose x = –3:   25 = A(–3 + 3)² + B(–3 – 2)(–3 + 3) + C(–3 – 2)   ⇒ 25 = A(0)² + B(–5)(0) + C(–5)   ⇒ 25 = –5C  ⟹ C = –5. • To find B, expand the right-hand side:   A(x + 3)² = A(x² + 6x + 9),   B(x – 2)(x + 3) = B(x² + x – 6),   C(x – 2) = Cx – 2C. So we have:   25 = [A + B]x² + [6A + B + C]x + [9A – 6B – 2C]. But the left side is a constant (no x or x² terms), so the coefficients of x² and x must be zero: 1) Coefficient of x²: A + B = 0 ⟹ 1 + B = 0 ⟹ B = –1. 2) Coefficient of x: 6A + B + C = 0 ⟹ 6(1) – 1 – 5 = 0 ⟹ 0 = 0 (check). 3) Constant term: 9A – 6B – 2C = 25 ⟹ 9 + 6 + 10 = 25 ⟹ 25 = 25 (check). Thus, the partial fractions decomposition is:   25/[(x – 2)(x + 3)²] = 1/(x – 2) – 1/(x + 3) – 5/(x + 3)². Step 3. Find the integral of 25/[(x – 2)(x + 3)²]: We need to evaluate   ∫ [1/(x – 2) – 1/(x + 3) – 5/(x + 3)²] dx. Integrate term by term: 1) ∫ 1/(x – 2) dx = ln|x – 2| + C₁. 2) ∫ [–1/(x + 3)] dx = –ln|x + 3| + C₂. 3) ∫ [–5/(x + 3)²] dx = –5∫ (x + 3)^(–2) dx. Recall: ∫ u^(–2) du = –u^(–1) + C, so with u = x + 3:   –5∫ (x + 3)^(–2) dx = –5 [–(x + 3)^(–1)] = 5/(x + 3) + C₃. Thus, the integral becomes:   ln|x – 2| – ln|x + 3| + 5/(x + 3) + C. Putting it all together, one acceptable answer is:   ∫ 25/[(x – 2)(x + 3)²] dx = ln|(x – 2)/(x + 3)| + 5/(x + 3) + C. This is the required result.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To express \( \frac{25}{(x-2)(x+3)^{2}} \) in the form \( \frac{A}{x-2}+\frac{B}{x+3}+\frac{C}{(x+3)^{2}} \), we start by setting up the equation: \[ \frac{25}{(x-2)(x+3)^{2}} = \frac{A}{x-2} + \frac{B}{x+3} + \frac{C}{(x+3)^{2}}. \] To combine the right side, we find a common denominator, which is \((x-2)(x+3)^{2}\): \[ \frac{A(x+3)^{2} + B(x-2)(x+3) + C(x-2)}{(x-2)(x+3)^{2}}. \] Now, we have: \[ 25 = A(x+3)^{2} + B(x-2)(x+3) + C(x-2). \] Next, we want to determine \(A\), \(B\), and \(C\). We can use convenient values of \(x\) to solve for these coefficients. 1. Set \(x = 2\): \[ 25 = A(2+3)^{2} \implies 25 = A(5)^{2} \implies 25 = 25A \implies A = 1. \] 2. Set \(x = -3\): \[ 25 = B(-3-2)(-3+3) + C(-3-2) \implies 25 = -5C \implies C = -5. \] 3. To find \(B\), substitute \(A\) and \(C\) back into the original equation. Let's use \(x = 0\): \[ 25 = 1(0+3)^{2} + B(0-2)(0+3) - 5(0-2). \] This gives: \[ 25 = 1(9) + B(-2)(3) + 10 \implies 25 = 9 - 6B + 10 \implies 25 = 19 - 6B \implies 6B = -6 \implies B = -1. \] Now we have: \[ A = 1, \quad B = -1, \quad C = -5. \] Thus, we can express \( \frac{25}{(x-2)(x+3)^{2}} \) as: \[ \frac{1}{x-2} - \frac{1}{x+3} - \frac{5}{(x+3)^{2}}. \] Next, we integrate: \[ \int \frac{25}{(x-2)(x+3)^{2}} \, dx = \int \left( \frac{1}{x-2} - \frac{1}{x+3} - \frac{5}{(x+3)^{2}} \right) \, dx. \] This results in: \[ \int \frac{1}{x-2} \, dx - \int \frac{1}{x+3} \, dx - 5 \int \frac{1}{(x+3)^{2}} \, dx. \] Calculating each part: 1. \( \int \frac{1}{x-2} \, dx = \ln |x-2| + C_1 \), 2. \( \int \frac{1}{x+3} \, dx = \ln |x+3| + C_2 \), 3. \( \int \frac{1}{(x+3)^{2}} \, dx = -\frac{1}{x+3} + C_3 \). Putting it all together, the final result of the integral is: \[ \ln |x-2| - \ln |x+3| + \frac{5}{x+3} + C. \] Thus, the integral of \( \frac{25}{(x-2)(x+3)^2} \) is: \[ \ln \left| \frac{x-2}{x+3} \right| + \frac{5}{x+3} + C. \]

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad